PENGEMBANGAN PENDIDIKAN ANTIKORUPSI BERBASIS KANTIN KEJUJURAN DI SEKOLAH DASAR - Imam Nawawi (Universitas Negeri Malang, 2016)
Abstract: The study aims at finding the pattern of the right development of anti-corruption education through the use of honest school canteen system (kantin kejujuran) for primary school students. The study was done in descriptive qualitative and also quantitative study. The data were obtained through giving the questionnaire to the headmasters and teachers at primary school. Both of qualitative and quantitative data from teachers and students were analysed in the descriptive analysis. The result of the study showed that honest school canteen system (kantin kejujuran ) can help primary school students to internalize discipline and honesty values. In conclusion, the development of anti-corruption education at primary schools has to be integrated into classroom activities and real-life activities at school. Abstrak: Penelitian ini bertujuan menemukan pola pengembangan pendidikan antikorupsi yang tepat melalui pemanfaatan kantin kejujuran bagi para siswa Sekolah Dasar. Penelitian ini dilakukan secara deskriptif kualitatif maupun kuantitatif. Pengambilan data menggunakan angket yang ditujukan pada kepala sekolah dan para guru kelas. Data penelitian ini dianalisis secara deskriptif, baik berupa data kuantitif maupun data kualitatif, data dari guru maupun data dari siswa. Hasil penelitian ini menunjukkan bahwa kantin kejujuran sebagai proses internalisasi nilai kejujuran dan kedisiplinan anak SD. Kesimpulannya pengembangan pendidikan antikorupsi di sekolah dasar perlu dilaksanakan secara terintegrasi dengan berbagai teme pembelajaran di kelas dan praktik kehidupan di sekolah.